Prep & Landing ; Prep & Landing : Naughty vs. nice - McKim, Dorothy; Wermers, Stevie; Deters, Kevin; Chalke, Sarah; Richardson, Derek, 1976-; Parnell, Chris, 1967-; Foley, Dave, 1963-; Walt Disney Pictures; Buena Vista Home Entertainment (Firm) (Burbank, Calif. : Distributed by Buena Vista Home Entertainment, 2012)
Prep & Landing: On Christmas Eve, a high-tech team of elves from an elite unit known as 'Prep & Landing' ensures homes around the world are prepared for Santa's visit. But when two hilarious little elves face unexpected challenges and are pushed to their limits, it'll take a great big effort to save the season.
Prep & Landing: Naughty vs. nice: The outrageous yuletide adventures of Christmas elves Lanny and Wayne continue in this totally tinsel adventure that reminds us there's room for everyone on the nice list. Santa's stealthiest little elves must race to recover classified North Pole technology which has fallen into the hands of a computer-hacking naughty kid, in an effort to stop Christmas from descending into chaos.
DVD feature: Prep & Landing (ca. 23 min) -- Prep & Landing: Naughty vs. nice (ca. 23 min.) -- Bonus.
Collection includes two short animation films Prep & Landing (ca. 23 min.) and Prep & Landing: Naughty vs. nice (ca. 23 min.) in two media versions: DVD and BD.
Originally broadcast on television in 2009 and 2011.
Special features include featurettes: Operation: secret Santa; Tiny's big adventure; Behind the jingle; Kringle Academy; North Pole news; North Pole commentaries; promotional pieces.
Music, Michael Giacchino.
Dave Foley, Sarah Chalke, Derek Richardson, Emily Alyn Lind, Chris Parnell.
Rating: TVG CHV rating: G.
Keywords: Santa Claus -- (Fictitious character) -- Juvenile films; Elves -- Juvenile films; Holidays -- Juvenile films; Hackers -- Juvenile films; Animated films; Animated television programs; Children's films; Children's television programs; Feature films; Fiction films; Fiction television programs; Juvenile works; Video recordings for the hearing impaired